Dual site‐controlled two‐photon fluorescent probe for the imaging of lysosomal pH in living cells. (6th September 2018) - Wang, Chao; Dong, Baoli; Kong, Xiuqi; Zhang, Nan; Song, Wenhui; Lin, Weiying
Abstract: Abnormal lysosomal pH is closely associated with many diseases, and real‐time monitoring of lysosomal pH is important for understanding the lysosome physiological nature. Here, we present a novel lysosome‐targeting two‐photon fluorescent probe (MP‐lys ) for monitoring pH changes in living cells. As a dual site‐controlled probe, MP‐lys employed morpholine and piperazine groups as the lysosome‐targeting groups and pH response sites.MP‐lys showed rapid, reversible and sensitive fluorescence response to pH.MP‐lys possessed lysosome‐targeting properties, and could be used for two‐photon imaging of chloroquine‐induced pH variation in living cells.